Impact of the COVID‐19 pandemic on Otolaryngology trainee education. Issue 10 (15th July 2020) - Guo, Theresa; Kiong, Kimberley L.; Yao, Christopher M. K. L.; Windon, Melina; Zebda, Denna; Jozaghi, Yelda; Zhao, Xiao; Hessel, Amy C.; Hanna, Ehab Y.
Abstract: Background: The COVID‐19 pandemic has reduced clinical volume with a negative impact on trainee education. Methods: Survey study of Otolaryngology trainees in North America, during the COVID‐19 pandemic in April 2020. Results: Of 216 respondents who accessed the survey, 175 (83%) completed the survey. Respondents reported a universal decrease in clinical activities (98.3%). Among participants who felt their program utilized technology well, there were significantly decreased concerns to receiving adequate educational knowledge (29.6% vs 65.2%, P = .003). However, 68% of trainees still expressed concern in ability to receive adequate surgical training. In addition, 54.7% of senior trainees felt that the pandemic had a negative impact on their ability to secure a job or fellowship after training. Conclusions: Trainees universally felt a negative impact due to the COVID‐19 pandemic. Use of technology was able to alleviate some concerns in gaining adequate educational knowledge, but decreased surgical training remained the most prevalent concern.